2016
DOI: 10.1038/srep20318
|View full text |Cite
|
Sign up to set email alerts
|

Human oral isolate Lactobacillus fermentum AGR1487 induces a pro-inflammatory response in germ-free rat colons

Abstract: Lactobacilli are thought to be beneficial for human health, with lactobacilli-associated infections being confined to immune-compromised individuals. However, Lactobacillus fermentum AGR1487 negatively affects barrier integrity in vitro so we hypothesized that it caused a pro-inflammatory response in the host. We compared germ-free rats inoculated with AGR1487 to those inoculated with another L. fermentum strain, AGR1485, which does not affect in vitro barrier integrity. We showed that rats inoculated with AGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Numerous studies have reported that probiotics exert beneficial effects mainly through the recognition of the probiotics by TLRs, which activates corresponding signaling pathways and triggers appropriate responses [ 54 , 55 ]. The upregulation of the Nrf2 pathway, which protects against oxidative stress and injury, has been reported [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that probiotics exert beneficial effects mainly through the recognition of the probiotics by TLRs, which activates corresponding signaling pathways and triggers appropriate responses [ 54 , 55 ]. The upregulation of the Nrf2 pathway, which protects against oxidative stress and injury, has been reported [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have also reported that probiotics themselves can stimulate the immune system of the intestinal mucosa [70,71]. For example, Anderson et al (2016) showed that Lactobacillus fermentum AGR1487 can upregulate the expression of proin ammatory factors by activating the TLR signaling pathway and induce the in ammatory response in sterile rats. The different effects of microorganisms on the intestinal mucosal immune system may be due to the differences between test conditions and strains [72].…”
Section: Discussionmentioning
confidence: 99%
“…Closely, Anderson et al. () reported a human oral strain of Lactobacillus fermentum (AGR 1487) induced a proinflammatory response by damaging mucosal barrier integrity. The association of common probiotic genera with inflammation highlights the necessity of deeper taxonomic resolution when considering host–microbial interactions.…”
Section: Discussionmentioning
confidence: 99%